Avaliação da atividade osteogênica da doxiciclina em uma matriz de compósito biodegradável de poli (-caprolactona), poli (ácido lático-co-glicólico) e biocerâmica in vitro - Vivianne Carvalho da Cunha (2012)
Composites of biodegradable polymers and bioceramics are an alternative in the area of tissue engineering for bone regeneration, since they combine the bioactivity of bioceramics with the flexibility of polymers. Doxycycline (DOX) is a broad spectrum antibiotic, has widespread use as an aid in periodontal therapy. DOX can suffer degradation under oscillation of pH, heat and humidity, and toxic effects. To overcome these problems, encapsulation systems with -cyclodextrin (CD) allows protection of the molecule and its controlled release, reducing the frequency of administration, effective therapeutic concentration and prolongs its therapeutic effect to allow for periodontal tissue regeneration. In this study, we evaluated composites of polycaprolactone (PCL), poly (lactic-co-glycolic acid) (PLGA) and bioceramics of biphasic calcium phosphate (BCP) loaded with doxycycline encapsulated in CD to evaluate its biocompatibility and activity on osteoblast cells. The composite BCP / PCL / PLGA / DOX / CD was prepared with double mixing method. The PCL and PLGA (50:50) were dissolved in dichloromethane (DMC) added and BCP in the ratio 1:4 (PCL + PLGA / BCP) with addition of DOX and DOX / CD complex decreasing concentrations between 25l/ml and 1l/ml. Cell viability / proliferation of osteoblasts was assessed using the MTT test (24h, 7 and 14 days) and alkaline phosphatase (FA) and collagen were evaluated 7 and 14 days with Von Kossa and 14 days. The structure of the composites was evaluated by Scanning Electron Microscopy (SEM). The results of MTT after tests showed increased cell proliferation in the presence of the composite BCP / PCL / PLGA / DOX / CD , 25l/ml concentration, which was statistically significant (p <0.05) compared to control in all experimental times, being higher in the second week. The results showed that the composite FA with DOX included statistically different (p <0.05) compared to control in all experimental times, with greater increases in FA observed in the second week. These results suggest the activity of osteoblasts during osteogenesis and is related to bone matrix deposition by these cells. The results of collagen production by cells osteblásticas was higher in the presence of composite and showed a statistically significant difference (p <0.05) compared to control, only the second week. These results suggest that the increased secretion of collagen is related to osteogenic activity. The cells produced more collagen during the study periods indicates that these cells underwent osteogenesis up to 14 days of cultivation, producing the extracellular matrix in the presence of the composite. The results dialing Von Kossa cells undergoing osteogenic induction in the presence of the composite showed visually osteogenic activity of the cells through the formation of nodules of mineralization within 14 days. The evaluation of the composite porous architectural structure by SEM shows that the surface topography can be suitable for the cultivation of osteoblasts. These results indicate that the cells were viable in the presence of the composite BCP / PCL / PLGA / DOX / CD, promoting cell proliferation and osteogenic activity for its application in bone tissue engineering.